Mechanism of Thyroid-Hormone Regulated Expression of the SERCA Genes in Skeletal Muscle: Implications for Thermogenesis. Issue 2 (April 2001) - Simonides, Walter S.; Thelen, Marc H. M.; van der Linden, C. Gerard; Muller, Alice; van Hardeveld, Cornelis
Abstract : Thyroid hormone increases the Ca 2+ -ATPase activity of the sarcoplasmic reticulum (SR) in skeletal muscle, thereby increasing the energy-turnover associated with Ca 2+ -cycling during contraction and rest. The fast-muscle isoform of the Ca 2+ -ATPase (SERCA1) and the slow-muscle isoform (SERCA2a), are encoded by two genes that are transcriptionally regulated by T3 . The SERCA1 isoform can be expressed to considerably higher levels than the SERCA2a isoform. The stimulation of transcription of the SERCA1 gene by T3 is mediated by two thyroid hormone response elements, located in the promoter of this gene. The intracellular [Ca 2+ ] can modulate the effect of T3 . The increase in SR Ca 2+ -ATPase activity seen when T3 -levels rise above normal, results from the induction of SERCA1 expression in slow muscle fibers. Concomitant high levels of Ca 2+ -ATPase activity are associated with down-regulation of SERCA2a expression in these fibers. The observed T3 -dependent increase in SERCA1 expression and associated Ca 2+ -ATPase activity will increase the overall metabolic rate of the organism significantly under normal conditions, because of the high average level of contractile activity of slow fibers. Given the rise in serum T3 -levels during prolonged cold exposure, these data suggest that fiber-specific stimulation of SERCA1 expression contributes to the thermogenic response in non-shivering thermogenesis. This mechanism may be particularly relevant in larger mammals, which have a relatively high percentage of slow fibers in skeletal muscle, and which need to rely on tissues other than brown fat for the generation of extra heat.